Delays in diagnosis for children with newly diagnosed central nervous system tumors. Issue 4 (9th March 2018) - Coven, Scott L; Stanek, Joseph R; Hollingsworth, Ethan; Finlay, Jonathan L
Abstract: Background: United States studies documenting time interval from symptom onset to definitive diagnosis for childhood central nervous system (CNS) tumors are more than a quarter-century old. The purpose of this study is to establish an accurate and contemporary Ohio baseline of the diagnostic interval for children with newly diagnosed CNS tumors. Methods: Medical records were retrospectively reviewed for 301 children with newly diagnosed CNS tumors from January 2004 to August 2015 at Nationwide Children's Hospital. We obtained comprehensive data on 171 patients (56.8%). Records were reviewed for age, gender, tumor type, presenting symptoms, number of health care visits prior to diagnosis, time interval (in months) from onset of symptoms to definitive diagnosis, and any associated genetic syndromes. Results: Of the 171 patients with newly diagnosed CNS tumors, 25 children (14.6%) had a known cancer predisposition syndrome (all with neurofibromatosis type 1). Among the remaining 146 children, the median and mean time intervals from symptom onset to definitive diagnosis were 42 days and 138 days (range < 1 to 2190 days), respectively. Conclusions: We have documented and quantified the contemporary delays in diagnosis of childhood brain tumors in central Ohio to serve as a benchmark for our future planned interventions to reduce the time interval from symptom onset to diagnosis through adaptation of the United Kingdom HeadSmart program throughout the state of Ohio and ultimately throughout the United States.